2020
DOI: 10.1186/s13287-020-01865-7
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord-derived mesenchymal stem cells ameliorate insulin resistance via PTEN-mediated crosstalk between the PI3K/Akt and Erk/MAPKs signaling pathways in the skeletal muscles of db/db mice

Abstract: Background Globally, 1 in 11 adults have diabetes mellitus, and 90% of the cases are type 2 diabetes mellitus. Insulin resistance is a central defect in type 2 diabetes mellitus, and although multiple drugs have been developed to ameliorate insulin resistance, the limitations and accompanying side effects cannot be ignored. Thus, more effective methods are required to improve insulin resistance. Methods In the current study, db/m and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“… 39 , 40 Many studies showed that the PI3K‐AKT‐mTOR and MAPK pathways might crosstalk at various stages of signal transduction. 41 , 42 , 43 , 44 Surprisingly, our study showed that the PI3K‐AKT‐mTOR pathway regulated ACD without influencing apoptosis and that the MAPK pathway was involved in apoptosis without impacting ACD in ATG9b‐overexpressing HSCs. The results indicate that a change in the PI3K‐AKT‐mTOR pathway via activators affects apoptosis to a lesser extent than ATG9b overexpression and that the change in the MAPK pathway via inhibitors affects ACD to a lesser degree than ATG9b overexpression.…”
Section: Discussionmentioning
confidence: 67%
“… 39 , 40 Many studies showed that the PI3K‐AKT‐mTOR and MAPK pathways might crosstalk at various stages of signal transduction. 41 , 42 , 43 , 44 Surprisingly, our study showed that the PI3K‐AKT‐mTOR pathway regulated ACD without influencing apoptosis and that the MAPK pathway was involved in apoptosis without impacting ACD in ATG9b‐overexpressing HSCs. The results indicate that a change in the PI3K‐AKT‐mTOR pathway via activators affects apoptosis to a lesser extent than ATG9b overexpression and that the change in the MAPK pathway via inhibitors affects ACD to a lesser degree than ATG9b overexpression.…”
Section: Discussionmentioning
confidence: 67%
“…MSCs with exendin-4 have also shown significant alleviation of diabetic cardiomyopathy relative to the use of MSCs alone (Wassef et al 2018 ). hUCMSCs are believed to be a valuable option for disease therapy (Chen et al 2020 ). However, whether hUCMSCs@Ex-4 can be applied in the treatment of T1DM has not been addressed and was thus explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The db/db mouse is a genetic model of type II diabetes mellitus and it exhibits the typical features of human Type 2 diabetes mellitus [ 33 - 35 ]. Therefore, these mice were used to investigate the development of diabetic complications including cognitive impairment, vascular endothelial dysfunction, and enhanced ischemia-reperfusion-induced myocardial injury.…”
Section: Discussionmentioning
confidence: 99%